The Kunitz 1 and Kunitz 3 domains of tissue factor pathway inhibitor are required for efficient inhibition of factor Xa - Peraramelli, Sameera; Suylen, Dennis P. L.; Rosing, Jan; Hackeng, Tilman M. (Thrombosis and Haemostasis, 2012)
Tissue factor pathway inhibitor (TFPI) is a slow tight-binding inhibitor that inhibits factor (F)Xa in a biphasic fashion: a rapid formation of loose FXa•TFPI encounter complex is followed by slow rearrangement into a tight FXa•TFPI* complex in which the Kunitz-2 (K2) domain of TFPI binds and inhibits FXa. In the current study, full-length TFPI (TFPIfl) and various truncated TFPI constructs were used to assess the importance of TFPI domains other than K2 in the inhibition of FXa. In the absence of Ca2+ ions, FXa was more effectively inhibited by TFPIfl than Gladomain less FXa. In turn, Ca2+ ions impaired FXa inhibition by TFPIfl but not by TFPI constructs that lack the C-terminus. This suggests that, in absence of Ca2+ ions, interactions between the C-terminus of TFPI and the Gla-domain of FXa promote FXa-inhibition. TFPIfl and K2K3 had similar efficiencies for encounter complex formation. However, K2K3 showed monophasic inhibition instead of biphasic inhibition, indicating absence of rearrangement into a tight complex. K1K2 and TFPI1–161 showed biphasic inhibition, but had less efficient encounter complex formation than TFPIfl. Finally, K2K3 was a 10-fold more efficient FXainhibitor than K2. These results indicate that K3-C-terminus enhances the formation of encounter complex and that K1 is required for isomerisation of the encounter- into tight complex. Since TFPIfl has a 10-fold higher Ki than K2K3-C-terminus, we propose that K1 is not only required for the transition of the loose to the tight FXa•TFPI* complex, but also inhibits FXa•TFPI encounter complex formation. This inhibitory activity is counteracted by K3 and C-terminus.
Keywords: Anticoagulant; TFPI; protein S; factor Xa